The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1159/000125726
|View full text |Cite
|
Sign up to set email alerts
|

Underfeeding Alters the Effect of Low Levels of Estradiol on Luteinizing Hormone Pulsatility in Ovariectomized Female Rats

Abstract: Reduced food intake results in altered reproductive function in female mammals and previous studies have shown this to be due, at least in part, to an increase in the negative feedback efficacy of estrogen on pituitary luteinizing hormone (LH) secretion. This study attempted to elucidate the site (CNS vs. pituitary) of increased negative feedback efficacy of 17β-estradiol (E2) in underfed female rats. Rats (Holtzman) were fed either ad libitum (CR) or 50% of normal food intake (UR). All other condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous studies (6,24) demonstrated that the greater the E2 dose to OVX rats, the greater the suppression of pulsatile LH secretion during fasting. This implies a negative feedback effect of estrogen, which tonically suppresses LHRH or LH release in intact animals.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies (6,24) demonstrated that the greater the E2 dose to OVX rats, the greater the suppression of pulsatile LH secretion during fasting. This implies a negative feedback effect of estrogen, which tonically suppresses LHRH or LH release in intact animals.…”
Section: Discussionmentioning
confidence: 92%
“…In the sheep (6,45), rat (28,41), hamster (5,24,37), and monkey (14), the latter change reduced GnRH-dependent LH pulsatility. Insulin concentrations also fell (see below), as expected, in response to caloric deficiency.…”
Section: Discussionmentioning
confidence: 94%
“…mammalian species (55). Several endocrine and metabolic cues that are affected by caloric intake (i.e., glucose, leptin, insulin, and steroid hormones) are known to modulate LH secretion (1,15,41,42). Also, calorie restriction seems to enhance the negative feedback actions of estradiol on pulsatile GnRH and LH secretion (30,41), possibly by altering estrogen receptivity in the hypothalamus (24).…”
Section: Discussionmentioning
confidence: 99%
“…Return of menses has been observed in patients with primary hypothalamic amenorrhoea treated with naltrexone over an extended period of time (Wildt & Leyendecker, 1987), although the protocol and the small number of cases limit the conclusions. In rats naloxone could prevent the effect of starvation on the oestradiol-induced central nervous system effects (Spillar & Piacsek, 1991). Although the detailed mechanism of opiate action is not known, rat studies suggest the involvement of the morphin ^-receptors (/i-R) (Dyer et ai, 1985;Martini et al, 1989).…”
Section: Effect Of Nutritional Status On the Htgmentioning
confidence: 99%
“…Recent studies have yielded new information. Spillar & Piacsek (1991) studied 45day-old female rats randomly assigned to a control or a moderately underfed group. After 12 days no more pulses could be observed in the underfed group, while LH pulses depended on the oestradiol level in the control group.…”
Section: Effect Of Nutritional Status On the Htgmentioning
confidence: 99%